Serological evidence of Francisella tularensis in febrile patients seeking treatment at remote hospitals, Northeastern Kenya, 2014-2015 - Njeru, J.; Tomaso, H.; Mertens, K.; Henning, K.; Wareth, G.; Heller, R.; Kariuki, S.; Fèvre, Eric M.; Neubauer, H.; Pletz, M.W. (Elsevier, 2017)
Tularemia is a highly contagious infectious zoonosis caused by the bacterial agent Francisella tularensis. The aim of this study was to investigate the presence of antibodies to Francisella tularensis in febrile patients in northeastern Kenya. During 2014-2015, 730 patients were screened for anti-Francisella tularensis antibodies using a combination of ELISA and western blot (WB). Twenty seven (3.7%) patients were positive for F. tularensis. Tularemia was not suspected by the treating clinicians in any of those patients. Our results suggest that tularemia may be present in Kenya but remain unreported, and emphasizes the need for local clinicians to broaden their diagnostic repertoire when evaluating patients with undifferentiated febrile illness.